Experimental Study on Destroy of Dolos Armored Breakwater, Pacitan in Indonesia - Yanan Xu; Chen Hanbao; Ge Longzai (International Journal of Marine Engineering Innovation and Research, 2022)
The breakwater armored with 15 T Dolos block had destroyed several times during constructing even the section verified by experiment study in wave flume, and it was destroyed again after the repair design and test verification. The damage phenomena were compared between on site and in the lab. In the third model test study, it proposed the problems of rod broken caused by block shaking and rolling impact, as well as overall sliding caused by small block supporting the big block. The stability of the repair plan was verified again by increasing the block weight, and the section was verified under the wave impact after on-site implementation. The study also revealed the fact that shaking led to the broken of the rod and the breakwater failure.